EXPLORING THE KETOGENIC DIET: IMPACTS, CONTROVERSIES IN METABOLIC SYNDROME MANAGEMENT AND BEYOND (Uz Conferences, 2025)
This review article provides a comprehensive examination of the ketogenic diet (KD), a high-fat, low-carbohydrate dietary regimen, and its potential role in managing metabolic syndrome (MetS). The KD’s effectiveness in significantly impacting weight loss, BMI, glucose levels, insulin levels, HOMA-IR, HbA1c, total cholesterol, triglycerides, AST, and ALT is discussed. The article also explores the controversies surrounding the KD, including potential side effects and its role in cancer treatment. Future research directions, such as the link between the KD and the gut microbiome and its use in treating cardiovascular diseases, are highlighted. The article concludes by emphasizing the need for personalization in the KD and the necessity for long-term clinical trials to determine if the short-term effects of the KD translate into beneficial long-term outcomes